2021
DOI: 10.3390/nu13124218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Docosahexaenoic Acid (DHA) at the Enteric Level in a Synucleinopathy Mouse Model

Abstract: The aggregation of alpha-synuclein protein (αSyn) is a hallmark of Parkinson’s disease (PD). Considerable evidence suggests that PD involves an early aggregation of αSyn in the enteric nervous system (ENS), spreading to the brain. While it has previously been reported that omega-3 polyunsaturated fatty acids (ω-3 PUFA) acts as neuroprotective agents in the brain in murine models of PD, their effect in the ENS remains undefined. Here, we studied the effect of dietary supplementation with docosahexaenoic acid (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 113 publications
(146 reference statements)
1
1
0
Order By: Relevance
“…Analyses of microgliosis also revealed that the increase in the inflammatory response with aging in male mice was significant only in the SNCA-OVX types. Our results are in accordance with a previously reported increase in microgliosis in a Thy1-αSyn mouse model [ 21 , 74 ]. These increases in gliosis in synucleinopathy models can be explained by the possible interaction of αSyn with astrocytes and microglia [ 75 ].…”
Section: Discussionsupporting
confidence: 94%
“…Analyses of microgliosis also revealed that the increase in the inflammatory response with aging in male mice was significant only in the SNCA-OVX types. Our results are in accordance with a previously reported increase in microgliosis in a Thy1-αSyn mouse model [ 21 , 74 ]. These increases in gliosis in synucleinopathy models can be explained by the possible interaction of αSyn with astrocytes and microglia [ 75 ].…”
Section: Discussionsupporting
confidence: 94%
“…Omega-3 fatty acids, and particularly DHA, can interact with α-synuclein to prevent its detrimental oligomerization [ 72 , 73 , 74 ]. Another pathway of action of DHA is the modulation of dopamine-induced neurodegeneration [ 75 , 76 ] and the enhancement of anti-oxidative pathways [ 76 ].…”
Section: Neuroprotective Properties Of Dha-containing Phospholipidsmentioning
confidence: 99%